2013
DOI: 10.1080/19768354.2013.769897
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of the sand shrimpCrangon hakodateiRathbun, 1902 (Decapoda: Crangonidae) in the East Sea of Korea

Abstract: The feeding habits of the sand shrimp Crangon hakodatei in the East Sea (Korea) were investigated through analysis and comparison of the stomach contents of 602 individuals according to season, shrimp size class, and prey diversity. The diet of C. hakodatei consisted of 17 prey categories mainly comprising crustaceans, molluscs, polychaetes, nematodes, algae, and fishes, with crustaceans dominating the diet. Molluscs, nematodes, and fishes were also important prey, whilst other categories including polychaetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Crangon hakodatei is carnivorous, similar to other members of the genus Crangon (Campos et ak, 2012;Maher, 2013). Ontogénie changes in the diet have been found to shift from a diet based on small organisms during juvenile stages to larger macrofauna when in adults (Campos et ah, 2012).…”
Section: Role In the Foodwebmentioning
confidence: 97%
See 4 more Smart Citations
“…Crangon hakodatei is carnivorous, similar to other members of the genus Crangon (Campos et ak, 2012;Maher, 2013). Ontogénie changes in the diet have been found to shift from a diet based on small organisms during juvenile stages to larger macrofauna when in adults (Campos et ah, 2012).…”
Section: Role In the Foodwebmentioning
confidence: 97%
“…Ontogénie changes in the diet have been found to shift from a diet based on small organisms during juvenile stages to larger macrofauna when in adults (Campos et ah, 2012). Previous analyses on the stomach content of C. hakodatei revealed that a diversity of prey organisms were consumed by C. hakodatei, including polychaetes, molluscs and crustaceans (Wei & Liu, 1965;Tang & Ye, 1990;Amara & Paul, 2003;Maher et al" 2013), some ophiurians, juvenile fish or pelagic fry, nematodes and occasionally holothurian Protankyra bidentata (Woodward & Barett, 1858), Sagitta sp., foraminifer and Coscinodiscus spp. (Cheng & Zhu, 1997;Maher et ak, 2013).…”
Section: Role In the Foodwebmentioning
confidence: 98%
See 3 more Smart Citations